2020
DOI: 10.1371/journal.pone.0230027
|View full text |Cite
|
Sign up to set email alerts
|

Safety, prosthesis wearing time and health-related quality of life of lower extremity bone-anchored prostheses using a press-fit titanium osseointegration implant: A prospective one-year follow-up cohort study

Abstract: Background We described safety and functional one-year follow-up outcomes of individuals with lower limb amputation treated with bone-anchored prostheses using titanium press-fit osseointegration implants. Methods All consecutive individuals treated between March 2015 and June 2018 with curved osseointegration femur implant (OFI-C) indicated for a long femoral remnant, gamma osseointegration femur implant (OFI-Y) indicated for a short femoral remnant, or osseointegration tibia implant (OTI) were eligible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 27 publications
0
49
0
2
Order By: Relevance
“…No exclusion criteria were applied for gender, ethnicity, height or functional level. A total of 13 TFAs fitted with a non-FDA approved press-fit implant were assessed in Sydney, Australia between Sept 2017 and Aug 2018 (i.e., Integral leg prosthesis, Eska Orthopedics GmbH, Germany; Osseointegration Prosthetic Limb, Permedica SPA, Italy) (Atallah et al, 2020). Each participant signed a written ethical consent form approved by research organization's human ethics committee (Human Research Ethics Committee Certificate No 1600000332, Queensland University of Technology, Brisbane, Australia).…”
Section: Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…No exclusion criteria were applied for gender, ethnicity, height or functional level. A total of 13 TFAs fitted with a non-FDA approved press-fit implant were assessed in Sydney, Australia between Sept 2017 and Aug 2018 (i.e., Integral leg prosthesis, Eska Orthopedics GmbH, Germany; Osseointegration Prosthetic Limb, Permedica SPA, Italy) (Atallah et al, 2020). Each participant signed a written ethical consent form approved by research organization's human ethics committee (Human Research Ethics Committee Certificate No 1600000332, Queensland University of Technology, Brisbane, Australia).…”
Section: Populationmentioning
confidence: 99%
“…Alternatively, TFAs could be fitted with bone-anchored prostheses (BAP) attached to an osseointegrated implant surgically inserted into the residual femur (Branemark et al, 2001;Pitkin, 2013). Several studies demonstrated that transfemoral BAP could improve functions and health-related quality of life, particularly for young and active individuals experiencing overwhelming socket issues (Atallah et al, 2020;Hagberg and Branemark, 2009;Hebert et al, 2017;Hoyt et al, 2020;Leijendekkers et al, 2017;van Eck and McGough, 2015). Management of residual soft tissues as well as risks of infections, loosening, periprosthetic fracture and breakage of osseointegrated implant parts are deemed acceptable by treating teams, although they are yet to be satisfactorily resolved (Atallah et al, 2018;Atallah et al, 2020;Hoyt et al, 2020;Kunutsor et al, 2018;van Eck and McGough, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, the most common adverse event following osseointegration is infection (Reif et al, 2021), which may require oral antibiotics, operative debridement with implant retention, or implant removal with additional debridement (Al Muderis et al, 2017). Prior investigations of post-osseointegration infection have reported postoperative occurrence rates and management (Al Muderis et al, 2017;Reif et al, 2021;Hoffmeister et al, 2017;Atallah et al, 2020). However, it is currently unknown to what extent UPIC impacts the risk of subsequent infection.…”
Section: Introductionmentioning
confidence: 99%
“…9 Today, bone-anchored prostheses (BAPs), directly attached to a percutaneous implant, have become an alternative to socketsuspended prostheses (SSPs), especially in patients who have undergone transfemoral amputation (TFA) for reasons other than vascular disease and who have difficulty obtaining adequate and comfortable socket suspension. [10][11][12][13] Among patients using BAPs, improvements in patient-reported outcomes with regard to prosthetic function and HRQL have been reported as compared to their previous situation, [14][15][16][17][18] although in conjunction with implantrelated complications. 14,[17][18][19][20][21] Health economic evaluations of BAPs have shown higher costs, fewer visits, and some gain of qualityadjusted life-years (QALYs) as measured by the use of SF-36/SF-6D and as compared to the SSPs.…”
Section: Introductionmentioning
confidence: 99%